Association between 25-hydroxyvitamin D concentrations and pubertal timing: 6–14-year-old children and adolescents in the NHANES 2015–2016 - Liu, Ziqin (Frontiers in Endocrinology, 2024)
Background: The association between 25(OH)D and pubertal timing has not been well studied. The aim of this study was to assess the relationship between 25(OH)D levels and pubertal timing in children. Methods: Participants aged 6-14 years who had available nutritional and serum sex hormone (total testosterone (TT) and estradiol (E2)) information (n =1318) were included. We conducted a cross-sectional analysis of the associations between 25(OH)D and sex steroid hormones among children in the National Health and Nutrition Examination Survey, 2015-2016. Puberty was indicated by high levels of steroid hormones (TT≥50 ng/dL in men, E2≥20 pg/ml in women) or menarche. Results: Serum 25(OH)D and pubertal status showed the same trend in both males and females. In the male population, the OR values of serum 25(OH)D between 50 and <75 and ≥75 nmol/L were 0.52 (0.25, 1.08) and 0.64 (0.23, 1.75), respectively, compared with serum 25(OH)D<50 nmol/L. The OR of serum 25(OH)D ≥50 nmol/L compared with <50 nmol/L was 0.54 (0.26, 1.10), and the P value was statistically significant (P=0.048). In the female population, when the serum 25(OH)D concentration was <50 nmol/L, the ORs corresponding to a serum 25(OH)D concentration between 50 and <75 and ≥75 nmol/L were 0.53 (0.29, 0.98) and 0.50 (0.19, 1.30), respectively. The OR of serum 25(OH)D≥50 nmol/L compared with <50 nmol/L was 0.52 (0.19, 0.96), and the P value was statistically significant (P=0.037). Conclusions: A lower 25(OH)D level was associated with earlier puberty in both girls and boys. There was a negative association between 25(OH)D concentrations and pubertal timing.